Neonatal readmissions at Saint-Pierre hospital, epidemiology and risk factors - Rambeloson, Setra H.; Rabevazaha, Ny A.; Rasamoelison, Rina J.; Rakotojoelimaria, Elsa H.; Robinson, Annick L. (International Journal of Contemporary Pediatrics, 2022)
Background: Newborn attendance at pediatric emergency departments has sharply increased in France since the early 2000s. Early discharge from maternity is the main risk factor. The purpose of this study was to describe the demographic and perinatal factors involved in the readmission to hospital of newborn babies in Southern reunion Island. Methods: This was a 13-month, single-center, case-control retrospective study (December 2015 to December 2016) carried out in the neonatal and pediatric intensive care units of the Saint-Pierre university hospital. Cases were represented by any newborn released from the maternity hospital and having been re-hospitalized. Controls were represented by newborns born during the same study period and not readmitted during their first month of life. One case was matched with a control. Results: We included 109 newborns. The re-hospitalization rate was 2.08%. The most common presentation were: fever (35.7%), and neurological symptoms (34.8%). The main etiologies were infections (33.9%), respiratory pathologies (24.7%), and breastfeeding difficulties (11.9%). Breastfeeding OR=0.53; 95% CI [0.30-0.92] (p=0.03) and neonatal pathologies during the stay in the maternity hospital OR=0.49; 95% CI [0.28-0.45] (p=0.016) were protective factors. Conclusions: The lack of identification of a risk factor encourages us to expand our study population and to look for other factors such as the medical and paramedical supervision of the mother-child couple during the postpartum period and the follow-up of the new born after leaving the maternity ward.